Two-Electron Reductive Carbonylation of Terminal Uranium(V) and Uranium(VI) Nitrides to Cyanate by Carbon Monoxide** - Cleaves, Peter A (Angew Chem Int Ed Engl, 2014)
Two-electron reductive carbonylation of the uranium(VI) nitride [U(Tren(TIPS))(N)] (2, Tren(TIPS)=N(CH(2)CH(2)NSiiPr(3))(3)) with CO gave the uranium(IV) cyanate [U(Tren(TIPS))(NCO)] (3). KC(8) reduction of 3 resulted in cyanate dissociation to give [U(Tren(TIPS))] (4) and KNCO, or cyanate retention in [U(Tren(TIPS))(NCO)][K(B15C5)(2)] (5, B15C5=benzo-15-crown-5 ether) with B15C5. Complexes 5 and 4 and KNCO were also prepared from CO and the uranium(V) nitride [{U(Tren(TIPS))(N)K}(2)] (6), with or without B15C5, respectively. Complex 5 can be prepared directly from CO and [U(Tren(TIPS))(N)][K(B15C5)(2)] (7). Notably, 7 reacts with CO much faster than 2. This unprecedented f-block reactivity was modeled theoretically, revealing nucleophilic attack of the π* orbital of CO by the nitride with activation energy barriers of 24.7 and 11.3 kcal mol(−1) for uranium(VI) and uranium(V), respectively. A remarkably simple two-step, two-electron cycle for the conversion of azide to nitride to cyanate using 4, NaN(3) and CO is presented.